Solve for y m=y^2-y

Math
m=y2-y
Rewrite the equation as y2-y=m.
y2-y=m
Move m to the left side of the equation by subtracting it from both sides.
y2-y-m=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=1, b=-1, and c=-m into the quadratic formula and solve for y.
1±(-1)2-4⋅(1⋅(-m))2⋅1
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Factor -1 out of (-1)2-4⋅(1⋅(-m)).
Tap for more steps…
Factor -1 out of (-1)2.
y=1±1-4⋅(1⋅(-m))2⋅1
Factor -1 out of -4⋅(1⋅(-m)).
y=1±1-(-4⋅(1⋅(m)))2⋅1
Factor -1 out of –1-(-4⋅(1⋅(m))).
y=1±-(-1-4⋅(1⋅(m)))2⋅1
y=1±-(-1-4⋅(1⋅(m)))2⋅1
Multiply m by 1.
y=1±-(-1-4m)2⋅1
y=1±-(-1-4m)2⋅1
Multiply 2 by 1.
y=1±-(-1-4m)2
y=1±-(-1-4m)2
The final answer is the combination of both solutions.
y=1+-(-1-4m)2
y=1–(-1-4m)2
Solve for y m=y^2-y

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top